2004
DOI: 10.1246/bcsj.77.1697
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fluorene Based Host Compounds Designed to Probe Solid-State Fluorescence

Abstract: Two novel host compounds, 2,7-bis(3-hydroxy-3,3-diphenylprop-1-ynyl)fluorene and 2,7-bis [3,3-(biphenyl-2,2 0 -diyl)-3-hydroxyprop-1-ynyl]fluorene have been synthesized. Many inclusion complexes of these host compounds with common volatile guests show solid-state fluorescence, which is ascribed to the existence of rigid dimers in the crystal structures, allowing excimer formation. Differential intermolecular interactions about the fluorescent moiety result in various colored emissions.Guest specific fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This has been supported by theoretical modeling (see below). The bulkiness of the substituents borne by the aryl rings play hence a crucial role in the tuning of the emission color of aryl‐substituted 2 c – g 55. Such remarkable tuning of the emission band by steric hindrance appears to be a simple and efficient way to tune the emission colors of aryl‐substituted DSF‐IFs 2 fluorophores.…”
Section: Resultsmentioning
confidence: 99%
“…This has been supported by theoretical modeling (see below). The bulkiness of the substituents borne by the aryl rings play hence a crucial role in the tuning of the emission color of aryl‐substituted 2 c – g 55. Such remarkable tuning of the emission band by steric hindrance appears to be a simple and efficient way to tune the emission colors of aryl‐substituted DSF‐IFs 2 fluorophores.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the p-p stacking interaction resulted in a silver complex displaying a highly electrical conducting behaviour, 34 and it also led to a change in the fluorescent emission intensity for some compounds. 35 In the area of magnetic coupling interactions, p-p stacking interaction also plays an important role. For example, some authors attributed the strong ferromagnetic order to p-p stacking interaction, 36 and other authors found the p-p stacking interaction led to a strong antiferromagnetic interaction between spin-carriers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the p-p stacking interaction resulted in a silver complex displaying a highly electrical conducting behaviour, 34 and it also led to a change in the fluorescent emission intensity for some compounds. 35 In the magnetic coupling area, some authors attributed the strong ferromagnetic order to p-p stacking, 36 and other authors found the p-p stacking interaction led to a strong antiferromagnetic interaction between mononu-clear Ni(II) complexes. 37 In a word, the p-p stacking interaction should be one of the key factors that dominate magnetic coupling, but neither a fitting formula nor theoretical calculations have been reported for the magnetic coupling of a p-p stacking interaction system as yet.…”
Section: Introductionmentioning
confidence: 99%